Preliminary Assessment of Low-cost Unmanned Aerial Systems (UAS) for Creating Aerial Photographs for Natural Resource Research - Compas, Eric (Proceedings of the Wisconsin Space Conference, 2016)
The recent significant reduction in the cost of unmanned aerial systems (UAS) has expanded access to this technology to researchers in a variety of fields. For aerial mapping, UAS holds the promise to substantially increase the resolution of imagery and provide better control over when imagery is produced. In the natural resources, UAS could greatly expand the type of research questions that can be asked at a relatively low cost. This research assessed the utility and characteristics of low-cost UAS aerial photography for natural resource applications. Four craft, Â commercial fixed-wing and multirotor and handbuilt fixed-wing and multirotor, were tested in this study. Our findings conclude that UAS aerial photography is approximately 10x more detailed than traditional aerial photography, but issues with spatial accuracy and available flight weather may limit its use for some applications.